The potential of utrophin and dystrophin combination therapies for Duchenne muscular dystrophy - Guiraud, S; Edwards, B; Babbs, A; Squire, S; Berg, A; Moir, L; Wood, M; Davies, K (Oxford University Press, 2019)
Duchenne muscular dystrophy (DMD) is a lethal neuromuscular disorder caused by loss of dystrophin. Several therapeutic modalities are currently in clinical trials but none will achieve maximum functional rescue and full disease correction. Therefore, we explored the potential of combining the benefits of dystrophin with increases of utrophin, an autosomal paralogue of dystrophin. Utrophin and dystrophin can be co-expressed and co-localized at the same muscle membrane. Wild-type (wt) levels of dystrophin are not significantly affected by a moderate increase of utrophin whereas higher levels of utrophin reduce wt dystrophin, suggesting a finite number of actin binding sites at the sarcolemma. Thus, utrophin upregulation strategies may be applied to the more mildly affected Becker patients with lower dystrophin levels. Whereas increased dystrophin in wt animals does not offer functional improvement, overexpression of utrophin in wt mice results in a significant supra-functional benefit over wt. These findings highlight an additive benefit of the combined therapy and potential new unique roles of utrophin. Finally, we show a 30% restoration of wt dystrophin levels, using exon-skipping, together with increased utrophin levels restores dystrophic muscle function to wt levels offering greater therapeutic benefit than either single approach alone. Thus, this combination therapy results in additive functional benefit and paves the way for potential future combinations of dystrophin- and utrophin-based strategies.